2011
DOI: 10.1016/j.pneurobio.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Iron, zinc and copper in the Alzheimer's disease brain: A quantitative meta-analysis. Some insight on the influence of citation bias on scientific opinion

Abstract: Dysfunctional homeostasis of transition metals is believed to play a role in the pathogenesis of Alzheimer’s disease (AD). Although questioned by some, brain copper, zinc, and particularly iron overload are widely accepted features of AD which have led to the hypothesis that oxidative stress generated from aberrant homeostasis of these transition metals might be a pathogenic mechanism behind AD. This meta-analysis compiled and critically assessed available quantitative data on brain iron, zinc and copper level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
187
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(193 citation statements)
references
References 75 publications
1
187
1
4
Order By: Relevance
“…Evidence that zinc accumulates in the brain during Alzheimer's disease While recent reviews have stated that zinc, iron, and copper accumulate in the cortex of AD patients (Bonda et al 2011b;Greenough et al 2012), a quantitative meta-analysis found decreased levels of copper and no significant difference in cortical zinc or iron (Schrag et al 2011b). Furthermore, a citation bias was found for studies reporting increased cortical iron.…”
Section: Risk Of Zinc Deficiency In the Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that zinc accumulates in the brain during Alzheimer's disease While recent reviews have stated that zinc, iron, and copper accumulate in the cortex of AD patients (Bonda et al 2011b;Greenough et al 2012), a quantitative meta-analysis found decreased levels of copper and no significant difference in cortical zinc or iron (Schrag et al 2011b). Furthermore, a citation bias was found for studies reporting increased cortical iron.…”
Section: Risk Of Zinc Deficiency In the Elderlymentioning
confidence: 99%
“…Disruption of mineral homeostasis has long been suspected as a pathological mechanism in AD and therapeutic strategies are now being aimed at restoring mineral homeostasis. Evidence regarding changes in the brain mineral distribution of AD patients is apparently conflicting (Schrag et al 2011b), and our understanding of the mechanisms regulating zinc distribution in the brain during normal development, aging, and disease remains incomplete. Nevertheless, preclinical studies and early clinical trials have provided encouragement for mineral targeted therapies in the treatment and prevention of AD (Constantinidis 1992;Ritchie et al 2003;Lannfelt et al 2008;Faux et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc content has been reported to be abnormally high in blood 165 and hippocampus 166 of AD patients. However, in the cerebrospinal fluid, zinc levels seem to be lowered in AD patients, 167 and globally in the brain, zinc levels have been reported to be unchanged 152 or reduced 168,169 in AD. Thus, zinc levels in AD are debatable, 170 and there is substantial heterogeneity in the reported zinc levels, 152 possibly due to sample heterogeneity, variable attention to free, chelatable Zn 2+ vs protein-bound Zn(II) pools, and redistributions within the brain as a function of disease progression and age.…”
mentioning
confidence: 99%
“…While total cortical iron levels may be unaltered in AD [137], post-mortem MRI and histopathological studies showed that increased iron levels are associated with amyloid-beta (Abeta) plaques [138,139], vessel walls, and microglia [140]. One of the possible sources of iron in AD are microbleeds related to cerebral amyloid angiopathy [141].…”
Section: Parkinson's and Alzheimer's Diseasesmentioning
confidence: 99%